Lung volume reduction surgery and lung transplantation in chronic obstructive pulmonary disease - Denis Hadjiliadis (International Journal of COPD, 2008)
Jorge I Mora1, Denis Hadjiliadis21Albert Einstein Medical Center, Philadelphia, PA, USA; 2Hospital of the University of Pennsylvania, Philadelphia, PA, USAAbstract: Medical treatment of emphysema does not alter the natural progression of the disease. Surgical techniques are an attractive conceptual approach to treat hyperinflation in these patients. Lung volume reduction surgery and lung transplantation are appropriate therapeutic options for a selected population with emphysema. We will review the available evidence to support these approaches.Keywords: COPD, emphysema, lung volume reduction, lung transplantation